The last patriot - Thor, Brad. (New York : Pocket Books, 2009)
Navy SEAL turned covert Homeland Security operative Scot Harvath must race to locate an ancient secret that has the power to stop militant Islam dead in its tracks.
Keywords: Koran -- Fiction; Harvath, Scot (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Terrorists -- Fiction; Suspense fiction